Deletion of Gpatch2 does not alter Tnf expression in mice - Destiny Dalseno; Holly Anderton; Andrew Kueh; Marco J Herold; John Silke; Andreas Strasser; Philippe Bouillet (Cell Death and Disease, 2023)
Abstract The cytokine TNF has essential roles in immune defence against diverse pathogens and, when its expression is deregulated, it can drive severe inflammatory disease. The control of TNF levels is therefore critical for normal functioning of the immune system and health. We have identified GPATCH2 as a putative repressor of Tnf expression acting post-transcriptionally through the TNF 3’ UTR in a CRISPR screen for novel regulators of TNF. GPATCH2 is a proposed cancer-testis antigen with roles reported in proliferation in cell lines. However, its role in vivo has not been established. We have generated Gpatch2 −/− mice on a C57BL/6 background to assess the potential of GPATCH2 as a regulator of Tnf expression. Here we provide the first insights into Gpatch2 −/− animals and show that loss of GPATCH2 affects neither basal Tnf expression in mice, nor Tnf expression in intraperitoneal LPS and subcutaneous SMAC-mimetic injection models of inflammation. We detected GPATCH2 protein in mouse testis and at lower levels in several other tissues, however, the morphology of the testis and these other tissues appears normal in Gpatch2 −/− animals. Gpatch2 −/− mice are viable, appear grossly normal, and we did not detect notable aberrations in lymphoid tissues or blood cell composition. Collectively, our results suggest no discernible role of GPATCH2 in Tnf expression, and the absence of an overt phenotype in Gpatch2 −/− mice warrants further investigation of the role of GPATCH2.